Partners for fish and wildlife program - Noonan, Bill, speaker; Morgan, Ken, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
The Partners program, since the mid-1980's, has been developing and maintaining positive working relationships with landowners to benefit fish and wildlife resources. Such activities have resulted in tremendous on-the-ground habitat restoration and enhancement accomplishments that contribute to the Service's federal trust resource mission and instill in our partners an even greater appreciation for fish, wildlife and the habitats upon which they depend. All of this is being accomplished in a voluntary manner. The program provides both technical and financial assistance to private landowners to achieve on-the-ground habitat restoration projects.
The partners for fish and wildlife program is the U.S. Fish and Wildlife Service's private lands program
The partners for fish and wildlife program is the U.S. Fish and Wildlife lands program
Moderator: Ken Morgan.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses